Application of Coastal and Marine Ecological Classification Standard to organize island ecosystem: the Abu Musa Island, Persian Gulf case study - ROUHOLLAH ZARE; MAHMOOD SINAEI; ARASH SHAKOURI; MEHDI BOLOUKI KOURANDEH; MOHAMMAD HASAN GERAMI (Society for Indonesian Biodiversity, 2017)
Abstract. Zare R, SinaeiM, ShakouriA, KourandehMB, GeramiMH. 2017. Application of Coastal and Marine Ecological Classification Standard to organize island ecosystem: the Abu Musa Island, Persian Gulf case study. Biodiversitas 18: 153-159. A first step in marine conservation plans is to identify and classify habitat types. These classifications should be scientificallyrigorous with high application. The Coastal and Marine Ecological Classification Standard (CMECS) is a nested, hierarchical framework that applies a uniform set of rules that have a high capacity in marine habitats classifications. In this study, this capacity was tested for the Abu Musa Island ecosystem, Persian Gulf. The Surface Geology Component and the Biotic CoverComponent were analyzed and encoded with the given instructions. In total, 21 codes were determined for benthic communities and 19 codes for geoform component, which showed high diversity of habitats and variety of biotopes in this island.Finally, results indicated that the CMECS approach was successful in Abu Musa habitat classification. In addition, results were very useful for sustainable development especially for ecotourism plans. Keywords: Abu Musa Island, CMECS, ecotourism, habitat classification